2016
DOI: 10.1016/j.dnarep.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Getting it done at the ends: Pif1 family DNA helicases and telomeres

Abstract: It is widely appreciated that the ends of linear DNA molecules cannot be fully replicated by the conventional replication apparatus. Less well known is that semi-conservative replication of telomeric DNA also presents problems for DNA replication. These problems likely arise from the atypical chromatin structure of telomeres, the GC-richness of telomeric DNA that makes it prone to forming DNA secondary structures, and from RNA-DNA hybrids, formed by transcripts of one or both DNA strands. Given the different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 84 publications
2
38
0
Order By: Relevance
“…Beyond the response to oxidative stress, yeast PIF1 is known to have essential roles at chromosome ends (telomeres), ribosomal DNA maintenance, and Okazaki fragment processing (for review, see [184186]). With advances pointing toward an important role of Pif1 in nuclear as well as mitochondrial DNA metabolism in yeast, Futami et al first reported the localization of human Pif1 in mitochondria as well as nuclei [187].…”
Section: Dna Helicases and The Metabolism Of Mitochondrial Oxidativelmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the response to oxidative stress, yeast PIF1 is known to have essential roles at chromosome ends (telomeres), ribosomal DNA maintenance, and Okazaki fragment processing (for review, see [184186]). With advances pointing toward an important role of Pif1 in nuclear as well as mitochondrial DNA metabolism in yeast, Futami et al first reported the localization of human Pif1 in mitochondria as well as nuclei [187].…”
Section: Dna Helicases and The Metabolism Of Mitochondrial Oxidativelmentioning
confidence: 99%
“…This area seems to be greatly understudied, and we anxiously await progress to learn if Pif1 modulates 5’ flap processing during BER in the mitochondria where oxidative stress is prominent. This seems a reasonable possibility, as a number of studies indicate a role of Pif1 in Okazaki fragment processing and telomere maintenance by virtue of its ability to efficiently unwind 5’ flap DNA structures, a key intermediate of long patch BER, as mentioned above (for review, see [184186]). Given that predicted G4 DNA structures believed to impede DNA synthesis are abundant in eukaryotic nuclear and mitochondrial genomes [188192], it seems probable that PIF1 plays an important role to resolve such mtDNA structures in human cells, as evidence already implicates the homolog in nuclear DNA replication through G4 sequences in S. cerevisiae [193] and S. pombe [9].…”
Section: Dna Helicases and The Metabolism Of Mitochondrial Oxidativelmentioning
confidence: 99%
“…These structures include stable protein complexes, highly transcribed genes and stable DNA secondary structures1. Paused replication forks are particularly susceptible to breakage owing to the single-stranded DNA at the fork.…”
mentioning
confidence: 99%
“…In the engineered yeast system harboring large CAG expansions [185], loss of Rad51, Rad52, Mre11, Pif1, and Mus81 and/or Yen1 proteins suppressed TNR expansion, all of which are proteins of BIR and recombination pathways [183,184]. Pif1 prevents replication- fork stalling at G-quadruplexes [186]. The factors that promote expansion are members of the recombination machinery.…”
Section: Encountering Bubbles and Breaks Within Tnrsmentioning
confidence: 99%